Teaching Factory Learning Model as Income Generating Unit with Marketable Products in Public Vocational High School - Mentari, Febiana Putri; Nurhadi, Didik; Patmanthara, Syaad (Fakultas Teknik Universitas Negeri Malang, 2021)
Vocational High School (VHS) is a vocational school intended to give students practical skills to create skilled graduates ready for jobs. To serve this purpose, Public Vocational High School (PVHS) 1 of Jenangan designs teaching factory learning model. Teaching factory is a learning model focusing on teaching students some practical skills with which to manufacture quality products up to industry standard. Hopefully, the educational outcome of this model can be Income Generating Unit (IGU) of software engineering study program in the school. This is descriptive and qualitative research using Miles ad Huberman’s data analysis model. The research found that using teaching factory as income generating unit with marketable products in software engineering study program is an effective strategy for the effort to provide quality human resources ready to perform jobs and create marketable products.